Path curve design for cancellation of singularities of two-degree-of-freedom planar parallel robots - Önal, Sinan Yalçın (My University, 2023)
Paralel robotlar, konvansiyonel seri robotlara göre birçok avantaja sahiptir. Bu sayede alma ve yerleştirme, montaj, paketleme, kaynak, takım tezgahları, koordinat ölçüm makineleri, hareket simülatörleri, tıbbi ve cerrahi uygulamalar, haptik cihazlar, mikrorobotik, uzay, uydu ve anten sistemleri ve tarım gibi birçok alanda kullanılmaktadır. En büyük dezavantajları ise çalışma alanları içinde yer alan Tip II tekilliklerdir. Klasik robot kollarda görülmeyen, sadece paralel robotlara özgü bu tekilliklere yaklaşırken aktüasyon torklarının ve/ veya kuvvetlerinin büyüklükleri sonsuza gider. Literatürde bu tekillik probleminin çözümüne yönelik yapılmış pek çok araştırma mevcuttur. Fakat buna rağmen, paralel robotların dinamik denklemlerinin Tip II tekil konumlardaki tutarlılığı ile geometrik yol özellikleri arasındaki ilişki üzerine yayınlanmış herhangi bir çalışma bulunmamaktadır. Bu tezde, Tip II tekilliklerden geçen iki serbestlik dereceli düzlemsel paralel robotlar için bir geometrik yol planlama yöntemi geliştirilmiştir. Geliştirilen yol planlama yöntemi, 5R düzlemsel paralel robot üzerine bir örnekle sayısal olarak test edilmiş ve doğrulanmıştır.

Parallel robots have many advantages compared to conventional serial robots. Thanks to these advantages, they are used in many areas like pick and place, assembly, packaging, welding, machine tools, coordinate measuring machines, motion simulators, medical and surgical applications, haptic devices, microrobotics, space, satellite and antenna systems, and agriculture. Their biggest disadvantage is the presence of Type II singularities inside the workspace. While getting close to these singularities, which are not seen in classical robotic arms and are unique to parallel robots, the magnitudes of the required actuator torques and/ or forces go to infinity. There are many researches conducted in the literature to solve this singularity problem. However, there is no published study on the relationship between the consistency of the dynamic equations of parallel robots at Type II singular positions and the geometrical path properties. In this thesis, a geometric path planning method is developed for two-degree-of-freedom planar parallel robots crossing Type II singularities. The developed path planning method is numerically tested and verified with an example on the 5R planar parallel robot.
İki serbestlik dereceli düzlemsel paralel robotların tekilliklerinin kaldırılması için yol eğrisi tasarımı
Keywords: Makine mühendisliği; Mechanical engineering; Paralel manipülatörler; Paralel robotlar; Parallel manipulators; Parallel robots; Path planning; Robotlar; Singularity; Tekillik; Yol planlama Robots